Study of the structural stability of the Nb–Cr alloy upon cyclic microdeformation; The Physics of Metals and Metallography; Vol. 118, iss. 3 - Lyubimova L. L. Lyudmila Leonidovna; Tashlykov A. A. Aleksandr Anatolievich; Makeev A. A. Anatoly Anatoljevich; Zavorin A. S. Aleksandr Sergeevich (2017, 2017)
Title screen